(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
The article analyzes the interpretations of the problem of women’s fate in Virginia Woolf’s essay-story “A Private Room”, Zulfiya Kurolboy kizi’s novels “Oyimtilla”, “The Captive of Armon”, and several short stories on a comparative basis.